Employees’ attitude towards Islamic banking: An exploratory study in Malaysia - Hassan, Arif (2016)
There are evidence to suggest that not all who work within Islamic banking system are fully convinced of its objectives and underlying philosophy. Good numbers of them have conventional banking background with little operational knowledge etc. Their ambivalent attitude may affect their work commitment. This study tries to understand the seriousness of this issue and explores the reasons behind this. Additionally, the research probed any possible association of employees’ attitude towards Islamic banking with their organizational commitment.